The Role of Islamic Financial and Digital Literacy in Shaping Economic Morality among MSMEs - Ibrohim Abdul Halim; Sayid Salahuddin Alaydrus; AA Hubur; Soeharjoto Soeharjoto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy. Despite their contribution to economic growth and employment, many MSMEs continue to face various challenges. This study examines the role of Islamic Financial Literacy and Digital Literacy in shaping the Economic Morality of MSMEs. Drawing upon the perspective of Islamic economics, Economic Morality is understood as ethical behavior in economic activities reflected through values such as honesty, fairness, responsibility, and concern for others. The study employs a quantitative approach using survey data collected from 89 MSME actors in Indonesia. Ordinary Least Squares regression is used to analyze the relationship between Islamic Financial Literacy, Digital Literacy, and Economic Morality. The findings indicate that Islamic Financial Literacy has a positive and significant effect on Economic Morality. When disaggregated into its dimensions, Awareness and Ability emerge as significant predictors, while Intention and Confidence do not demonstrate consistent effects. Digital Literacy also exhibits a positive and significant relationship with Economic Morality, suggesting that digital capability complements Islamic financial knowledge in fostering ethical economic behavior. These findings extend the literature by demonstrating that Islamic Financial Literacy contributes not only to financial and business outcomes but also to the moral dimension of entrepreneurial behavior. The study highlights the importance of strengthening both Islamic financial literacy and digital literacy as part of broader efforts to develop financially capable and ethically responsible MSMEs.